2016
DOI: 10.3390/min6010022
|View full text |Cite
|
Sign up to set email alerts
|

The Growth of Gypsum in the Presence of Hexavalent Chromium: A Multiscale Study

Abstract: Abstract:The sorption of dissolved inorganic pollutants into the structure of minerals is an important process that controls the mobility and fate of these pollutants in the Earth's crust. It also modifies the surface structure and composition of the host mineral, affecting its crystallization kinetics. Here, we investigate the effect of hexavalent chromium, Cr(VI), on the nucleation and growth of gypsum by conducting two types of experiments: (i) in situ atomic force microscopy (AFM) observations of the growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Additionally, this finding is consistent with (i) the results from differential PDF analysis above where calcite accounts for most of the difference between pure and doped-ettringite phases and (ii) thermodynamic equilibrium calculations using PHREEQC that suggest that CrO 4 2– favors incorporation into a calcite–CaCrO 4 solid solution rather than an ettringite–Cr-ettringite solid solution (see the Supporting Information for PHREEQC details and results). Several studies have shown that calcite can readily accommodate CrO 4 2– in the CO 3 2– site. Therefore, these results suggest that, when IO 3 – and CrO 4 2– are co-mingled in a system where ettringite and calcite are readily formed, (i) IO 3 – will partition primarily into the ettringite phase and CrO 4 2– into the calcite phase and (ii) the presence and concentration of oxyanions will influence the mineralogical composition of the solid phase.…”
Section: Results and Discussionsupporting
confidence: 47%
“…Additionally, this finding is consistent with (i) the results from differential PDF analysis above where calcite accounts for most of the difference between pure and doped-ettringite phases and (ii) thermodynamic equilibrium calculations using PHREEQC that suggest that CrO 4 2– favors incorporation into a calcite–CaCrO 4 solid solution rather than an ettringite–Cr-ettringite solid solution (see the Supporting Information for PHREEQC details and results). Several studies have shown that calcite can readily accommodate CrO 4 2– in the CO 3 2– site. Therefore, these results suggest that, when IO 3 – and CrO 4 2– are co-mingled in a system where ettringite and calcite are readily formed, (i) IO 3 – will partition primarily into the ettringite phase and CrO 4 2– into the calcite phase and (ii) the presence and concentration of oxyanions will influence the mineralogical composition of the solid phase.…”
Section: Results and Discussionsupporting
confidence: 47%
“…In Figure (a) the step bunches or macro-steps are visible on the surface of the crystals as dark lines, indicating that the growth is directed by advancing the steps. As the macro-steps have a slower speed than the elementary steps, , those are generally observed in the middle of the primary step. Figure (b), on the other hand, shows that the presence of REE ions in the solution have caused a dramatic change on the step motion and therefore the final morphology of the crystals; the REE slowed the velocity of the steps or even blocked their advance.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is well-known that both inorganic , and organic additives , affect the nucleation, crystallization, and morphologies of gypsum crystals. To date, primarily the role that elements like Cr 3+ , Cu 3+ , Cr 6+ , Al 3+ , and Fe 3+ have on gypsum growth from solution have been studied. In contrast, a mechanistic understanding of the effect that major ions in, for example, brines or formation waters (e.g., Na + , K + , Li + , Cl – , or Mg 2+ ) has on gypsum crystallization is still lacking. Existing data from studies that address the crystallization of calcium sulfate phases in the presence of these ions are highly discrepant, and whether these ions become structurally incorporated or only surface adsorbed into the growing gypsum is still debated.…”
Section: Introductionmentioning
confidence: 99%